Correlation between triglyceride-glucose index and early neurological deterioration in patients with acute mild ischemic stroke - Liu, Yang; Wang, Zhiye; Zhang, Zuonian; Lu, Zhaomin; Zhang, Lihua; Ding, Wei; Fang, Kai; Pan, Xijin; Ni, Mengyuan; Liu, Junjun (Frontiers in Neurology, 2024)
ObjectiveThe Triglyceride-glucose Index (TyG) index is a dependable metric for assessing the degree of insulin resistance, serving as a standalone predictor of ischemic stroke risk, but its precise relationship with early neurological deterioration (END) remains incompletely expounded within the context of acute mild ischemic stroke patients. This research is to examine the correlation of the TyG index with END among patients experiencing acute mild ischemic stroke in China.MethodsThis retrospective analysis was conducted to systematically gather data regarding patients experiencing their maiden episode of acute mild ischemic stroke and hospitalized at the Neurology Department of Nanjing Meishan Hospital, located in Nanjing, Jiangsu Province, China, over the period extending from January 2020 to December 2022. The severity of stroke was determined through the utilization of the National Institutes of Health Stroke Scale (NIHSS) scores upon their admission. Demographic characteristics were collected, and measurements of fasting blood glucose, blood lipids, and glycosylated hemoglobin Alc levels were taken. END was defined as a one-point rise in the motor item function score on the NIHSS or a two-point increase in the overall score during the initial 72 h of hospitalization. For evaluating the correlation of the TyG index with END, a multivariate logistic regression analysis was carried out. To investigate whether there is a nonlinear relationship between the TyG index and END, smoothed curves were utilized.ResultsThe study included 402 patients diagnosed with acute mild ischemic stroke, with a mean age of 66.15 ± 10.04 years. Within this population, 205 were males (51.00%) and 197 were females (49.00%). Among these patients, 107 (26.62%) experienced END within 72 h of admission. Patients who developed END showed higher levels of the TyG index in comparison to those who remained stable (9.18 ± 0.46 vs. 8.87 ± 0.46, p < 0.001). In a comprehensive multivariate logistic regression analysis, the TyG index positively correlates with END (OR = 3.63, 95% CI: 1.75–7.54, p = 0.001). Furthermore, individuals in the fourth TyG index quartile exhibited a 2.36-fold heightened risk of END compared to those in the first quartile (95% CI: 1.38–8.19, p = 0.008). TyG index has a linear correlation with END in the generalized additive model (Log likelihood ratio test, p = 0.525).ConclusionOur findings demonstrate that TyG index has a significant, independent, and positive correlation with END in Chinese individuals diagnosed with acute mild ischemic stroke. This underscores the TyG index’s potential usefulness as a valuable risk stratification tool for stroke patients.